(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The representation of rural India in Indian English novels occupies a significant position in the literary landscape, offering deep insights into the socio-economic, cultural, and psychological realities of village life. Indian English novelists have portrayed rural spaces as complex sites marked by poverty, caste hierarchies, gender oppression, agrarian struggles, superstition, and social transformation. Through realistic narratives and empathetic characterization, writers such as Mulk Raj Anand, R. K. Narayan, and Bhabani Bhattacharya have vividly depicted the hardships, resilience, and cultural richness of rural communities. Their novels explore the lived experiences of marginalized groups, including peasants, laborers, untouchables, and women, foregrounding issues of exploitation, social injustice, and economic deprivation. At the same time, contemporary writers extend this portrayal by examining the effects of modernization, migration, globalization, and environmental challenges on rural life. This study aims to critically analyze how Indian English novels represent rural India and how these literary depictions contribute to social awareness, cultural understanding, and national consciousness. By blending realism with social critique, Indian English fiction provides a powerful platform for voicing rural concerns and reimagining pathways toward social change and inclusive development.